PRELIMINARY RESULTS OF THE STUDY OF THE MESILITHIC SITES LOCATED ON THE EASTERN SHORE OF LAKE CHASHKINSKOE - Lychagina, E.L.; Mitroshin, E.N. (Perm Federal Research Centre Journal, 2017)
Lake Chashkinskoye is an oxbow formation of the left bank of the River Kama. On the left shore of the lake, there are 5 archaeological sites known, which belong to the Mesolithic era. These are Chashkinskoe Lake V, Chashkinskoe Lake X, Chashkinskoe Lake XI, Zaposelye, a Mesolithic complex of Zaposelye settlement. The article considers the results of the studies carried out in 2014-2016 years on Chashkinskoe Lake X and Chashkinskoe Lake XI. Both sites were discovered during E.N. Mitroshin’s archaeological exploration in 2014. On the site of Chashkinskoe Lake X a test pit was split, which gave an impressive collection (153 items) of waste production of stone tools. The excavations in 2016 confirmed the legitimacy of attributing the site to a silicon processing workshop. On the site of Chashkinskoe Lake XI a test pit was dug in 2015 and, as a result, 38 stone artefacts were found. The trasological analysis of the collection helped identify 40 tools. The leading group of tools consisted of knives for cutting meat (fish) and bone carvers. During the excavation in 2016, of an area of 16 m2, 272 stone items were found. The preliminary analysis lets us attribute the site to a short-term site for hunters. The studies in 2014-2016 have helped to reveal two new types of sites: a silicon processingworkshop and a short-term site for hunters.